AN INVESTIGATION OF PHYSICOCHEMICAL PARAMETERS AND PHYTOPLANKTON COMMUNITY STRUCTURE OF EKO-NDE RESERVOIR IN OSUN STATE, NIGERIA - Akinyemi, Suwebat; Chia, Mathias; Jimoh, Mahboob; Okpanachi, Ibrahim; Oyeleke, Dolapo (FUDMA JOURNAL OF SCIENCES, 2022)
This research was carried out to determine the relationship between physicochemical variables and phytoplankton community of the Eko-Nde reservoir. Changes in physicochemical parameters of aquatic ecosystems have significant impact on the species that live therein. Eko-Nde reservoir is of socio-economic significance to communities that surround it, which necessitates a proper study of the phytoplankton composition and environmental status of the reservoir. Water samples were collected from two stations in the reservoir from January 2019 to August 2019. The physicochemical parameters that were determined include but not limited to temperature, total hardness, pH and biochemical oxygen demand. The composition and diversity of phytoplankton were analyzed. A total of 2039 cells ml-1 belonging to four (4) major divisions were dominant in the order; Bacillariophyta (898 cells ml-1) > Charophyta (788 cells ml-1) > Chlorophyta (302 cells ml-1) > Cyanophyta (51 cells ml-1). Principal Component Analysis and Canonical Corresponding Analysis showed that certain physicochemical variables such as temperature, pH and total hardness were key drivers of the phytoplankton community structure of the reservoir. Diversity indices showed moderate abundance and distribution of phytoplankton species, with the highest diversity of species in the months associated with the rainy season. The appearance of pollution tolerant species such as Anabaena circinalis, Oscillatoria limosa, Nitzschia gracilis, Cymbella mexicana, Pediastrum boryanum, Synedra ulna, Cyclotella meneghiniana and Gomphonema spp. suggest that the reservoir was on the verge of pollution. Anthropogenic activities around the reservoir should be closely monitored to avoid health risks to humans and endangerment of aquatic organisms.